High-elasticity polyester degradable plastic film and preparation method thereof
By modifying the combination of polylactic acid, dihydrosphingosine and bile acid, combined with nano-silica and other materials, a highly elastic polyester-based degradable plastic film was prepared, solving the performance of existing degradable plastic films in high humidity environments The problem of degradation improves its mechanical properties and application range.
Patent Information
- Application Number
- CN202411749401.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The performance of existing biodegradable plastic films has deteriorated in high humidity environments, making it difficult to meet the long-term application needs in agriculture and packaging fields, and its mechanical properties and elasticity are poor.
Modified polylactic acid is mixed with polylactic acid and dihydrosphingosine in a specific proportion to form amide bonds, increasing flexibility and hydrophobicity, and adding bile acids to improve compatibility, combining nanosilica and cellulose nanofibers , vitamin E antioxidant and UV-326 ultraviolet absorber, and high elastic polyester-based biodegradable plastic film is prepared by twin-screw extrusion and tensile treatment.
It significantly improves the elasticity and moisture resistance of polylactic acid film, extends its service life in high humidity environments, and enhances its mechanical properties and application range.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyester materials, in particular to a high-elastic polyester degradable plastic film and a preparation method thereof. Background Art
[0002] The main feature of degradable plastic film is that it can be gradually decomposed in the natural environment through the action of microorganisms or physical and chemical processes such as photooxidation and hydrolysis, and finally converted into harmless substances such as carbon dioxide, water and biomass, which significantly reduces the long-term pollution of traditional plastic films to the environment. Traditional plastic films, such as polyethylene (PE) and polypropylene (PP), are widely used in agricultural production, packaging, construction and other fields, but their difficult-to-degrade properties have led to serious "white pollution". These plastic wastes accumulate in the natural environment for a long time, which not only destroys the soil structure and affects the growth of crops, but may also be accidentally eaten by wild animals, posing a threat to the ecosystem. In contrast, the emergence of degradable plastic films provides an effective way to solve the above problems.
[0003] Existing degradable plastic films are mainly made of bio-based degradable plastics. Polylactic acid is one of the commonly used raw materials. Polylactic acid itself has good biodegradability, but its mechanical properties and elasticity are relatively poor, and it has certain hygroscopicity and water vapor sensitivity, especially under high humidity conditions. It will accelerate the aging and degradation of the material, resulting in a decrease in material performance. In view of this, we propose a highly elastic polyester degradable plastic film and a preparation method thereof. Summary of the invention
[0004] The object of the present invention is to provide a highly elastic polyester degradable plastic film and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0005] To achieve the above object, the present invention provides a highly elastic polyester degradable plastic film, comprising the following components: 45-55 parts by weight of modified polylactic acid, 12-16 parts by weight of tributyl citrate, 0.3-0.5 parts by weight of bile acid, 1-5 parts by weight of nano silicon dioxide, 0.5-0.9 parts by weight of cellulose nanofibers, 0.1-0.5 parts by weight of vitamin E antioxidant, 0.1-0.3 parts by weight of UV-326 ultraviolet absorber and 2-6 parts by weight of talc; The modified polylactic acid is prepared by mixing polylactic acid and dihydrosphingosine in a mass ratio of 10:0.6-1.2.
[0006] Preferably, the preparation method of the modified polylactic acid is as follows: The dihydrosphingosine is dissolved in N,N-dimethylformamide to form a dihydrosphingosine solution, and then polylactic acid is added to a three-necked flask with a condenser, and N,N-dimethylformamide is added, and the mixture is heated to 50-70°C under magnetic stirring until the polylactic acid is completely dissolved to obtain a polylactic acid solution, and then N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine are added, and then the dihydrosphingosine solution is added dropwise while stirring and heated to 50-60°C, and the reaction is carried out for 6-12 hours, and the heating is stopped. The reaction mixture is poured into water for the reaction time to precipitate the product, and the solid product is collected by filtering with a Buchner funnel, and the product is washed with pure water. The washed product is placed in a vacuum drying oven and dried at 60-70°C to constant weight to obtain a product modified polylactic acid.
[0007] The carbonyl group in the polylactic acid molecular chain is coplanar with the adjacent oxygen atom and is very close to the adjacent carbon atom, making it difficult to rotate. Therefore, the molecular chain has poor flexibility, the material is hard and brittle, and has poor impact resistance. Polylactic acid is polymerized from lactic acid monomers and is sensitive to humidity. Its main chain contains a large number of ester bonds, which are easily hydrolyzed in water, causing the molecular chain to break. When the polylactic acid film is exposed to a high humidity environment, the hydrolysis rate will accelerate with the increase of moisture, causing the film to decompose too quickly and increase the water vapor permeability, affecting its water vapor barrier performance, resulting in significant changes in the material's performance in the short term, such as brittleness, loss of strength, and poor sealing, which in turn affects the shelf life and quality of the items in the package.
[0008] Dihydrosphingosine, namely D-threonine dihydrosphingosine, is a long-chain amino alcohol and an amphiphilic molecule. Its head contains an amino group and a hydroxyl group. These functional groups can form hydrogen bonds with water molecules, so it is hydrophilic. Its tail is a long hydrocarbon chain. This part of the structure does not interact with water, so it is hydrophobic. The primary amine group of dihydrosphingosine can form an amide bond through a condensation reaction with the carboxyl group of polylactic acid, thereby linking the long hydrocarbon chain to the polylactic acid. Since the long hydrocarbon chain has good flexibility and ductility, it can fill the gaps between polymer molecular chains, increase the distance between polymer chains to a certain extent, reduce the interaction force between molecules, and reduce the close stacking between molecules, thereby making the material softer and more elastic. When subjected to external force, it can absorb and disperse stress, thereby improving the elasticity of the material, and thus can improve the flexibility of polylactic acid. At the same time, the long hydrocarbon chain structure can form a hydrophobic barrier, reducing the chance of water penetrating into the interior of the polymer, thereby slowing down the hydrolysis rate of the ester bond, improving the application of polylactic acid film in high humidity environments, and expanding its application range; however, although the improvement in hydrophobicity effectively reduces the water sensitivity of polylactic acid, there is a problem of poor compatibility with other materials, so bile acid is added. Since bile acid is a natural emulsifier with amphiphilicity, it can effectively improve the compatibility problem between modified polylactic acid and other components, reduce phase separation, and enhance interfacial bonding, which significantly improves the mechanical properties of the film.
[0009] Preferably, the concentration of the dihydrosphingosine solution is 0.1-0.5M.
[0010] Preferably, the concentration of the polylactic acid solution is 1-5% w / v.
[0011] Preferably, the molar ratio of dihydrosphingosine to N,N'-dicyclohexylcarbodiimide is 1:1-1.2.
[0012] Preferably, the 4-dimethylaminopyridine accounts for 1-10% of the mass of N,N'-dicyclohexylcarbodiimide.
[0013] On the other hand, the present invention provides a method for preparing a highly elastic polyester degradable plastic film, which is used for any one of the highly elastic polyester degradable plastic films described above, comprising the following steps: Use a high-speed mixer to add modified polylactic acid, tributyl citrate, nano-silica, cellulose nanofibers, vitamin E antioxidant, UV-326 ultraviolet absorber and talcum powder, stir and mix at room temperature for 5-10 minutes to make it fully uniform, then add the mixed materials into a twin-screw extruder, set the extrusion temperature and extrusion speed, and during the extrusion process, press the melt into a thin sheet through a mold, use a cooling roller to quickly cool the film just out of the extruder to solidify it, control the temperature of the cooling medium at 10-20°C, place the cooled film on a stretching machine for biaxial stretching treatment, and finally cut and surface-treat the film. After completion, roll up and package the finished film to obtain a highly elastic polyester biodegradable plastic film.
[0014] Preferably, the extrusion temperature is 160-180° C., and the extrusion speed is 20-30 rpm.
[0015] Preferably, the stretching ratio of the biaxial stretching treatment is set to 3-5:1.
[0016] Preferably, the stretching speed of the biaxial stretching treatment is controlled at a strain rate of 5-10% per second.
[0017] Compared with the prior art, the present invention has the following beneficial effects: In the highly elastic polyester degradable plastic film and preparation method thereof, dihydrosphingosine is used to modify polylactic acid, and an amide bond is formed between the amino group and the carboxyl group on the dihydrosphingosine so that the dihydrosphingosine is linked to the polylactic acid. The long hydrocarbon chain of the dihydrosphingosine has good flexibility and ductility, thereby improving the elasticity of the polylactic acid. Combined with the hydrophobicity of the long hydrocarbon chain structure, the chance of water penetrating into the interior of the polymer is reduced, thereby slowing down the hydrolysis rate of the ester bond, improving the application of the polylactic acid film in a high-humidity environment, and expanding the scope of application. At the same time, the natural emulsifier bile acid is used to overcome the compatibility problem between the modified polylactic acid and other components, reduce the phase separation phenomenon, enhance the interface bonding force, and improve the mechanical properties of the film. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0019] The invention discloses a highly elastic polyester degradable plastic film, comprising the following components: 45-55 parts by weight of modified polylactic acid, 12-16 parts by weight of tributyl citrate, 0.3-0.5 parts by weight of bile acid, 1-5 parts by weight of nano silicon dioxide, 0.5-0.9 parts by weight of cellulose nanofibers, 0.1-0.5 parts by weight of vitamin E antioxidant, 0.1-0.3 parts by weight of UV-326 ultraviolet absorber and 2-6 parts by weight of talc; The modified polylactic acid is prepared by mixing polylactic acid and dihydrosphingosine in a mass ratio of 10:0.6-1.2.
[0020] Embodiment 1: A highly elastic polyester biodegradable plastic film and a preparation method thereof, comprising the following steps: Prepare the following components: 55 parts by weight of modified polylactic acid, 16 parts by weight of tributyl citrate, 0.5 parts by weight of bile acid, 5 parts by weight of nano-silicon dioxide, 0.9 parts by weight of cellulose nanofibers, 0.5 parts by weight of vitamin E antioxidant, 0.3 parts by weight of UV-326 ultraviolet absorber and 6 parts by weight of talc; The modified polylactic acid is prepared by mixing polylactic acid and dihydrosphingosine in a mass ratio of 10:0.6; the molar ratio of dihydrosphingosine to N,N'-dicyclohexylcarbodiimide is 1:1.2; 4-dimethylaminopyridine accounts for 10% of the mass of N,N'-dicyclohexylcarbodiimide; Dissolve dihydrosphingosine in N,N-dimethylformamide to form a dihydrosphingosine solution with a concentration of 0.5M, then add polylactic acid to a three-necked flask with a condenser, add N,N-dimethylformamide, and heat to 50°C under magnetic stirring until the polylactic acid is completely dissolved to obtain a polylactic acid solution with a concentration of 5% w / v, then add N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine, then dropwise add the dihydrosphingosine solution while keeping stirring, and heat to 50°C, react for 8h, stop heating, and pour the reaction mixture into water for the reaction time to precipitate the product, collect the solid product by filtering with a Buchner funnel, wash the product with pure water, put the washed product into a vacuum drying oven, and dry it at 70°C to constant weight to obtain the product modified polylactic acid; Use a high-speed mixer to add modified polylactic acid, tributyl citrate, nano-silica, cellulose nanofibers, vitamin E antioxidant, UV-326 ultraviolet absorber and talcum powder, stir and mix at room temperature for 10 minutes to make it fully uniform, then add the mixed materials into a twin-screw extruder, set the extrusion temperature to 180°C, and the extrusion speed to 30 rpm. During the extrusion process, the melt is pressed into a thin sheet through a mold, and a cooling roller is used to quickly cool the film just out of the extruder to solidify it. The temperature of the cooling medium is controlled at 10°C, and the cooled film is placed on a stretching machine for biaxial stretching treatment. The stretching ratio is set to 3:1, and the stretching speed is controlled at a strain rate of 10% per second. Finally, the film is cut and surface treated. After completion, the finished film is rolled up and packaged to obtain a highly elastic polyester biodegradable plastic film.
[0021] Embodiment 2: A highly elastic polyester degradable plastic film and a preparation method thereof, comprising the following steps: Prepare the following components: 55 parts by weight of modified polylactic acid, 16 parts by weight of tributyl citrate, 0.5 parts by weight of bile acid, 5 parts by weight of nano-silicon dioxide, 0.9 parts by weight of cellulose nanofibers, 0.5 parts by weight of vitamin E antioxidant, 0.3 parts by weight of UV-326 ultraviolet absorber and 6 parts by weight of talc; The modified polylactic acid is prepared by mixing polylactic acid and dihydrosphingosine in a mass ratio of 10:0.9; the molar ratio of dihydrosphingosine to N,N'-dicyclohexylcarbodiimide is 1:1.2; 4-dimethylaminopyridine accounts for 10% of the mass of N,N'-dicyclohexylcarbodiimide; Dissolve dihydrosphingosine in N,N-dimethylformamide to form a dihydrosphingosine solution with a concentration of 0.5M, then add polylactic acid to a three-necked flask with a condenser, add N,N-dimethylformamide, and heat to 50°C under magnetic stirring until the polylactic acid is completely dissolved to obtain a polylactic acid solution with a concentration of 5% w / v, then add N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine, then dropwise add the dihydrosphingosine solution while keeping stirring, and heat to 50°C, react for 8h, stop heating, and pour the reaction mixture into water for the reaction time to precipitate the product, collect the solid product by filtering with a Buchner funnel, wash the product with pure water, put the washed product into a vacuum drying oven, and dry it at 70°C to constant weight to obtain the product modified polylactic acid; Use a high-speed mixer to add modified polylactic acid, tributyl citrate, nano-silica, cellulose nanofibers, vitamin E antioxidant, UV-326 ultraviolet absorber and talcum powder, stir and mix at room temperature for 10 minutes to make it fully uniform, then add the mixed materials into a twin-screw extruder, set the extrusion temperature to 180°C, and the extrusion speed to 30 rpm. During the extrusion process, the melt is pressed into a thin sheet through a mold, and a cooling roller is used to quickly cool the film just out of the extruder to solidify it. The temperature of the cooling medium is controlled at 10°C, and the cooled film is placed on a stretching machine for biaxial stretching treatment. The stretching ratio is set to 3:1, and the stretching speed is controlled at a strain rate of 10% per second. Finally, the film is cut and surface treated. After completion, the finished film is rolled up and packaged to obtain a highly elastic polyester biodegradable plastic film.
[0022] Embodiment 3: A highly elastic polyester biodegradable plastic film and a preparation method thereof, comprising the following steps: Prepare the following components: 55 parts by weight of modified polylactic acid, 16 parts by weight of tributyl citrate, 0.5 parts by weight of bile acid, 5 parts by weight of nano-silicon dioxide, 0.9 parts by weight of cellulose nanofibers, 0.5 parts by weight of vitamin E antioxidant, 0.3 parts by weight of UV-326 ultraviolet absorber and 6 parts by weight of talc; The modified polylactic acid is prepared by mixing polylactic acid and dihydrosphingosine in a mass ratio of 10:1.2; the molar ratio of dihydrosphingosine to N,N'-dicyclohexylcarbodiimide is 1:1.2; 4-dimethylaminopyridine accounts for 10% of the mass of N,N'-dicyclohexylcarbodiimide; Dissolve dihydrosphingosine in N,N-dimethylformamide to form a dihydrosphingosine solution with a concentration of 0.5M, then add polylactic acid to a three-necked flask with a condenser, add N,N-dimethylformamide, and heat to 50°C under magnetic stirring until the polylactic acid is completely dissolved to obtain a polylactic acid solution with a concentration of 5% w / v, then add N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine, then dropwise add the dihydrosphingosine solution while keeping stirring, and heat to 50°C, react for 8h, stop heating, and pour the reaction mixture into water for the reaction time to precipitate the product, collect the solid product by filtering with a Buchner funnel, wash the product with pure water, put the washed product into a vacuum drying oven, and dry it at 70°C to constant weight to obtain the product modified polylactic acid; Use a high-speed mixer to add modified polylactic acid, tributyl citrate, nano-silica, cellulose nanofibers, vitamin E antioxidant, UV-326 ultraviolet absorber and talcum powder, stir and mix at room temperature for 10 minutes to make it fully uniform, then add the mixed materials into a twin-screw extruder, set the extrusion temperature to 180°C, and the extrusion speed to 30 rpm. During the extrusion process, the melt is pressed into a thin sheet through a mold, and a cooling roller is used to quickly cool the film just out of the extruder to solidify it. The temperature of the cooling medium is controlled at 10°C, and the cooled film is placed on a stretching machine for biaxial stretching treatment. The stretching ratio is set to 3:1, and the stretching speed is controlled at a strain rate of 10% per second. Finally, the film is cut and surface treated. After completion, the finished film is rolled up and packaged to obtain a highly elastic polyester biodegradable plastic film.
[0023] Embodiment 4: A highly elastic polyester degradable plastic film and a preparation method thereof, comprising the following steps: Prepare the following components: 55 parts by weight of modified polylactic acid, 12 parts by weight of tributyl citrate, 0.3 parts by weight of bile acid, 1 part by weight of nano-silicon dioxide, 0.5 parts by weight of cellulose nanofibers, 0.1 parts by weight of vitamin E antioxidant, 0.1 parts by weight of UV-326 ultraviolet absorber, and 2 parts by weight of talc; The modified polylactic acid is prepared by mixing polylactic acid and dihydrosphingosine in a mass ratio of 10:1.2; the molar ratio of dihydrosphingosine to N,N'-dicyclohexylcarbodiimide is 1:1; 4-dimethylaminopyridine accounts for 1% of the mass of N,N'-dicyclohexylcarbodiimide; Dissolve dihydrosphingosine in N,N-dimethylformamide to form a dihydrosphingosine solution with a concentration of 0.5M, then add polylactic acid to a three-necked flask with a condenser, add N,N-dimethylformamide, and heat to 50°C under magnetic stirring until the polylactic acid is completely dissolved to obtain a polylactic acid solution with a concentration of 5% w / v, then add N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine, then dropwise add the dihydrosphingosine solution while keeping stirring, and heat to 50°C, react for 8h, stop heating, and pour the reaction mixture into water for the reaction time to precipitate the product, collect the solid product by filtering with a Buchner funnel, wash the product with pure water, put the washed product into a vacuum drying oven, and dry it at 70°C to constant weight to obtain the product modified polylactic acid; Use a high-speed mixer to add modified polylactic acid, tributyl citrate, nano-silica, cellulose nanofibers, vitamin E antioxidant, UV-326 ultraviolet absorber and talcum powder, stir and mix at room temperature for 10 minutes to make it fully uniform, then add the mixed materials into a twin-screw extruder, set the extrusion temperature to 180°C, and the extrusion speed to 30 rpm. During the extrusion process, the melt is pressed into a thin sheet through a mold, and a cooling roller is used to quickly cool the film just out of the extruder to solidify it. The temperature of the cooling medium is controlled at 10°C, and the cooled film is placed on a stretching machine for biaxial stretching treatment. The stretching ratio is set to 3:1, and the stretching speed is controlled at a strain rate of 10% per second. Finally, the film is cut and surface treated. After completion, the finished film is rolled up and packaged to obtain a highly elastic polyester biodegradable plastic film.
[0024] Embodiment 5: A highly elastic polyester biodegradable plastic film and a preparation method thereof, comprising the following steps: Prepare the following components: 45 parts by weight of modified polylactic acid, 16 parts by weight of tributyl citrate, 0.5 parts by weight of bile acid, 5 parts by weight of nano-silicon dioxide, 0.9 parts by weight of cellulose nanofibers, 0.5 parts by weight of vitamin E antioxidant, 0.3 parts by weight of UV-326 ultraviolet absorber and 6 parts by weight of talc; The modified polylactic acid is prepared by mixing polylactic acid and dihydrosphingosine in a mass ratio of 10:1.2; the molar ratio of dihydrosphingosine to N,N'-dicyclohexylcarbodiimide is 1:1.2; 4-dimethylaminopyridine accounts for 10% of the mass of N,N'-dicyclohexylcarbodiimide; Dissolve dihydrosphingosine in N,N-dimethylformamide to form a dihydrosphingosine solution with a concentration of 0.5M, then add polylactic acid to a three-necked flask with a condenser, add N,N-dimethylformamide, and heat to 50°C under magnetic stirring until the polylactic acid is completely dissolved to obtain a polylactic acid solution with a concentration of 5% w / v, then add N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine, then dropwise add the dihydrosphingosine solution while keeping stirring, and heat to 50°C, react for 8h, stop heating, and pour the reaction mixture into water for the reaction time to precipitate the product, collect the solid product by filtering with a Buchner funnel, wash the product with pure water, put the washed product into a vacuum drying oven, and dry it at 70°C to constant weight to obtain the product modified polylactic acid; Use a high-speed mixer to add modified polylactic acid, tributyl citrate, nano-silica, cellulose nanofibers, vitamin E antioxidant, UV-326 ultraviolet absorber and talcum powder, stir and mix at room temperature for 10 minutes to make it fully uniform, then add the mixed materials into a twin-screw extruder, set the extrusion temperature to 180°C, and the extrusion speed to 30 rpm. During the extrusion process, the melt is pressed into a thin sheet through a mold, and a cooling roller is used to quickly cool the film just out of the extruder to solidify it. The temperature of the cooling medium is controlled at 10°C, and the cooled film is placed on a stretching machine for biaxial stretching treatment. The stretching ratio is set to 3:1, and the stretching speed is controlled at a strain rate of 10% per second. Finally, the film is cut and surface treated. After completion, the finished film is rolled up and packaged to obtain a highly elastic polyester biodegradable plastic film.
[0025] Embodiment 6: A highly elastic polyester biodegradable plastic film and a preparation method thereof, comprising the following steps: Prepare the following components: 50 parts by weight of modified polylactic acid, 16 parts by weight of tributyl citrate, 0.5 parts by weight of bile acid, 5 parts by weight of nano-silicon dioxide, 0.9 parts by weight of cellulose nanofibers, 0.5 parts by weight of vitamin E antioxidant, 0.3 parts by weight of UV-326 ultraviolet absorber and 6 parts by weight of talc; The modified polylactic acid is prepared by mixing polylactic acid and dihydrosphingosine in a mass ratio of 10:1.2; the molar ratio of dihydrosphingosine to N,N'-dicyclohexylcarbodiimide is 1:1.2; 4-dimethylaminopyridine accounts for 10% of the mass of N,N'-dicyclohexylcarbodiimide; Dissolve dihydrosphingosine in N,N-dimethylformamide to form a dihydrosphingosine solution with a concentration of 0.5M, then add polylactic acid to a three-necked flask with a condenser, add N,N-dimethylformamide, and heat to 50°C under magnetic stirring until the polylactic acid is completely dissolved to obtain a polylactic acid solution with a concentration of 5% w / v, then add N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine, then dropwise add the dihydrosphingosine solution while keeping stirring, and heat to 50°C, react for 8h, stop heating, and pour the reaction mixture into water for the reaction time to precipitate the product, collect the solid product by filtering with a Buchner funnel, wash the product with pure water, put the washed product into a vacuum drying oven, and dry it at 70°C to constant weight to obtain the product modified polylactic acid; Use a high-speed mixer to add modified polylactic acid, tributyl citrate, nano-silica, cellulose nanofibers, vitamin E antioxidant, UV-326 ultraviolet absorber and talcum powder, stir and mix at room temperature for 10 minutes to make it fully uniform, then add the mixed materials into a twin-screw extruder, set the extrusion temperature to 180°C, and the extrusion speed to 30 rpm. During the extrusion process, the melt is pressed into a thin sheet through a mold, and a cooling roller is used to quickly cool the film just out of the extruder to solidify it. The temperature of the cooling medium is controlled at 10°C, and the cooled film is placed on a stretching machine for biaxial stretching treatment. The stretching ratio is set to 3:1, and the stretching speed is controlled at a strain rate of 10% per second. Finally, the film is cut and surface treated. After completion, the finished film is rolled up and packaged to obtain a highly elastic polyester biodegradable plastic film.
[0026] Comparative Example 1: The method of Example 3 was adopted without adding dihydrosphingosine-modified polylactic acid.
[0027] Comparative Example 2: The method of Example 3 was adopted to modify the mixture of polycaprolactone and polylactic acid.
[0028] Comparative Example 3: The method of Example 3 was adopted without adding bile acid.
[0029] The present invention adopts a high elastic polyester type degradable plastic film prepared by using modified polylactic acid, wherein the performance index inspection items and inspection standards of the high elastic polyester type degradable plastic film are as follows: To test the moisture resistance of plastic film, the specific test steps are as follows: first record the mass of the sample before the test, then place the sample in the same humidity and temperature environment, set the conditions of 40°C and 90% relative humidity, and calculate the remaining mass of the sample after 30 days. The degradation residual rate (%) = (mass before the test - mass after 30 days) / mass before the test. In a high humidity environment, the faster the degradation rate, the worse the moisture resistance.
[0030] According to GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets", the tensile strength and elongation at break of the material are tested. Tensile strength refers to the maximum stress that the material can withstand during the stretching process, that is, the maximum force per unit area that the material can withstand before it breaks; elongation at break refers to the ratio of the increase in gauge length when the specimen breaks during the stretching process to the original gauge length. Tensile strength is an important parameter for measuring the ability of a material to resist an applied tensile force. For elastic materials, good tensile strength means that the material can remain intact under greater stress and is not prone to breakage; elongation at break directly reflects the ductility and elasticity of the material. A high elongation at break indicates that the material can withstand greater deformation without breaking.
[0031] The tear strength of materials is tested according to GB / T 16578-2008 "Determination of tear resistance of plastic films and sheets". Tear strength refers to the ability of a material to resist tear propagation. It is the force required to apply force to a specimen of a specific shape until the tear is fully developed. Tear strength is related to the overall toughness of the material. Especially for films and sheets, good tear strength means that the material can still maintain its integrity after being locally damaged.
[0032] According to the above standards, the highly elastic polyester degradable plastic films prepared in the above Examples 1-6 and Comparative Examples 1-3 were tested, and the obtained data are shown in Table 1: Table 1 Performance data of Examples 1-6 and Comparative Examples 1-3
[0033] The above data fully show that compared with Comparative Examples 1-3, Examples 1-6 can fully show the effect of modified polylactic acid on the elasticity and moisture resistance of high-elastic polyester degradable plastic films.
[0034] Since the present invention adopts modified polylactic acid to prepare the high elastic polyester degradable plastic film, the performance of the high elastic polyester degradable plastic film is effectively improved by modifying the polylactic acid, as follows: It can be seen from Examples 1-3 that as the proportion of the modified polylactic acid component continues to increase, the elasticity and moisture resistance are significantly improved, indicating that the reaction between dihydrosphingosine and polylactic acid can effectively improve the mechanical properties and elasticity of polylactic acid, and the flexible long hydrocarbon chains of dihydrosphingosine can fill the gaps between polymer molecular chains, increase the spacing between polymer chains, and reduce the close stacking between molecules, thereby making the film more elastic. At the same time, the hydrophobic structure of the long hydrocarbon chains of dihydrosphingosine reduces the chance of moisture penetrating into the interior of the polymer, slowing down the degradation rate of the polylactic acid film in a high humidity environment, thereby effectively increasing the scope of application, and thus the film and moisture resistance are significantly improved.
[0035] It can be seen from Examples 2 and 4 that with the continuous increase in the content of other components, there is no obvious change in elasticity and moisture resistance, indicating that small changes in other components within a certain range are not enough to significantly affect the elasticity and moisture resistance of the high-elastic polyester degradable plastic film, and therefore there is no obvious change.
[0036] It can be seen from Examples 2, 5 and 6 that as the content of modified polylactic acid continues to increase, the elasticity and moisture resistance are significantly improved, which further supports the conclusion that the reaction between dihydrosphingosine and polylactic acid can effectively improve the mechanical properties and elasticity of polylactic acid. It shows that after polylactic acid is modified with dihydrosphingosine, on the one hand, the flexible long hydrocarbon chain can help polylactic acid reduce the interaction force between molecules, provide free space for the movement of molecular chains, and improve the elastic properties of the film. On the other hand, it can form a layer of hydrophobic barrier to reduce the contact between ester groups and water molecules, thereby improving its water resistance.
[0037] According to the above test experiments, the highly elastic polyester degradable plastic film prepared according to Example 3 has the best performance, so Example 3 is taken as the best example; By comparing Example 3 with Comparative Examples 1-3, it can be seen that: In Comparative Example 1, no dihydrosphingosine-modified polylactic acid is added, and the elasticity and moisture resistance of the high-elastic polyester biodegradable plastic film are worse. Dihydrosphingosine forms amide bonds through condensation reaction with the carboxyl group of polylactic acid, which not only weakens the interaction force between molecular chains and improves the elastic properties of the film, but also introduces long hydrocarbon chains to increase the hydrophobicity of the material. Therefore, in the absence of dihydrosphingosine, the polylactic acid film lacks these structural improvements, exhibits higher rigidity and brittleness, and the characteristics of rapid hydrolysis in a high-humidity environment. It cannot effectively resist moisture and cannot be effectively used in a high-humidity environment, and has a narrow application range.
[0038] In comparative example 2, polycaprolactone and polylactic acid are added for mixed modification. The elasticity and moisture resistance of the high-elastic polyester degradable plastic film are poor. Although the mixed modification of polycaprolactone and polylactic acid can improve the elasticity of the material to a certain extent, the modification of polycaprolactone mainly relies on physical mixing to improve it, while dihydrosphingosine enhances the performance of the material through chemical structure changes. In addition, new chemical bonds are formed, and dihydrosphingosine can be more evenly distributed in the polylactic acid. Therefore, compared with the mixed modification of polycaprolactone and polylactic acid, the performance of dihydrosphingosine-modified polylactic acid is better.
[0039] In Comparative Example 3, bile acid is not added. Bile acid, as a natural emulsifier, can promote good dispersion and interface bonding between different components. A good dispersion state helps to reduce phase separation and enhance the synergistic effect between the components. Therefore, the lack of bile acid will lead to poor distribution of additives or fillers, resulting in local enrichment or depletion, affecting the overall consistency.
[0040] In summary, polylactic acid is modified by dihydrosphingosine and flexible long hydrocarbon chains are introduced into polylactic acid, which improves the flexibility and hydrophobicity of polylactic acid. The compatibility between components is improved by amphiphilic bile acid, thereby improving the consistency of the film. In addition, the added dihydrosphingosine and bile acid are both natural components with good biocompatibility, which not only effectively improves the elastic properties of polylactic acid, but also improves the application of polylactic acid in high humidity environments.
[0041] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only preferred examples of the present invention, and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A highly elastic polyester degradable plastic film, characterized in that: The invention comprises the following components: 45-55 parts by weight of modified polylactic acid, 12-16 parts by weight of tributyl citrate, 0.3-0.5 parts by weight of bile acid, 1-5 parts by weight of nano silicon dioxide, 0.5-0.9 parts by weight of cellulose nanofiber, 0.1-0.5 parts by weight of vitamin E antioxidant, 0.1-0.3 parts by weight of UV-326 ultraviolet absorber and 2-6 parts by weight of talc; The modified polylactic acid is prepared by mixing polylactic acid and dihydrosphingosine in a mass ratio of 10:0.6-1.
2.
2. The highly elastic polyester degradable plastic film according to claim 1, characterized in that: The preparation method of the modified polylactic acid is as follows: The dihydrosphingosine is dissolved in N,N-dimethylformamide to form a dihydrosphingosine solution, and then polylactic acid is added to a three-necked flask with a condenser, and N,N-dimethylformamide is added, and the mixture is heated to 50-70°C under magnetic stirring until the polylactic acid is completely dissolved to obtain a polylactic acid solution, and then N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine are added, and then the dihydrosphingosine solution is added dropwise while stirring and heated to 50-60°C, and the reaction is carried out for 6-12 hours, and the heating is stopped. The reaction mixture is poured into water for the reaction time to precipitate the product, and the solid product is collected by filtering with a Buchner funnel, and the product is washed with pure water. The washed product is placed in a vacuum drying oven and dried at 60-70°C to constant weight to obtain a product modified polylactic acid.
3. The highly elastic polyester degradable plastic film according to claim 2, characterized in that: The concentration of the dihydrosphingosine solution is 0.1-0.5M.
4. The highly elastic polyester degradable plastic film according to claim 2, characterized in that: The concentration of the polylactic acid solution is 1-5% w / v.
5. The highly elastic polyester degradable plastic film according to claim 2, characterized in that: The molar ratio of the dihydrosphingosine to N,N'-dicyclohexylcarbodiimide is 1:1-1.
2.
6. The highly elastic polyester degradable plastic film according to claim 2, characterized in that: The 4-dimethylaminopyridine accounts for 1-10% of the mass of N,N'-dicyclohexylcarbodiimide.
7. A method for preparing a highly elastic polyester degradable plastic film, used for preparing a highly elastic polyester degradable plastic film as claimed in any one of claims 1 to 6, characterized in that: The steps include: Use a high-speed mixer to add modified polylactic acid, tributyl citrate, bile acid, nano-silica, cellulose nanofibers, vitamin E antioxidant, UV-326 ultraviolet absorber and talcum powder, stir and mix at room temperature for 5-10 minutes to make it fully uniform, then add the mixed materials into a twin-screw extruder, set the extrusion temperature and extrusion speed, and during the extrusion process, press the melt into a thin sheet through a mold, use a cooling roller to quickly cool the film just out of the extruder to solidify it, control the temperature of the cooling medium at 10-20°C, place the cooled film on a stretching machine for biaxial stretching treatment, and finally cut and surface-treat the film. After completion, roll up and package the finished film to obtain a highly elastic polyester biodegradable plastic film.
8. The method for preparing a highly elastic polyester degradable plastic film according to claim 7, characterized in that: The extrusion temperature is 160-180° C., and the extrusion speed is 20-30 rpm.
9. The method for preparing a highly elastic polyester degradable plastic film according to claim 7, characterized in that: The stretching ratio of the biaxial stretching process is set to 3-5:
1.
10. The method for preparing a highly elastic polyester degradable plastic film according to claim 7, characterized in that: The stretching speed of the biaxial stretching process is controlled at a strain rate of 5-10% per second.
Citation Information
Patent Citations
Degradable flame-retardant plastic film and production process thereof
CN111690251A
A fully biodegradable composite film with high mechanical strength, its processing technology and its application
FR3098443A1
Biodegradable material, and film product and application thereof
US20240309205A1